OlivesApp: Aplicativo de Classificação do Índice de Maturação de Azeitonas através do YOLOv8 - Alvino, Diogo da Silva; Belarmino, Jhon Randler dos Santos; Junior, Warley M. Valente; Alves, Elton Rafael; Valente, Aline Santana Oliveira; Nunes, Cleiton Antônio; Anconi, Amanda Carolina Souza Andrada (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
This work presents the development of an application designed to detect and classify the ripeness index of olives using YOLOv8. The main objective is to provide a practical and accessible solution for olive growers and researchers, facilitating analysis and decision-making related to olive harvesting and cultivation. The application employs image processing algorithms to identify specific characteristics of olives in digital images, classifying their ripeness quickly and efficiently. The results indicate that the application has great potential to optimize production processes and improve the quality of olives and olive oil.